Effect of planting media and poultry manure fertilizier on Growth And Weight OF Lettuce - Lamdo, Herfandi; Anissa , Nabillah; Damsir , Damsir (Jurnal Pertanian, 2023)
Grelen lettluce is a vegeltable plalnt favolred by the peolple of Indolnesia whilch has nutrlitional, provitlamin A, potaslsium, and callcium (Suprliati & Herllina, 2014). Lettluce cultilvation reqluires nutrlients in the folrm of orglanic fertillizers to grlowth and devellopment. Poulltry manlure has the higlhest N, P and K contlent and is availlable molre quickly (Sari et al., 2016). Cocopeat is a planting medium that has very high absorption with a pH 5.0 – 6.8 and good for root growth (Fahmi, 2013). The purpose of this study was to obtain the right compositiovn of growing mediva with poltry manure for optimal growth and yield of green lettuce. The research at the Experimental Garden, Satu Nusa University of Lampung, from January to April 2023. The research method Factorial RAK, Factor 1 was poltry manure, P1 = 5 tons ha-1, P2 = 10 tons ha-1, P3 = 15 tons ha-1. Factor 2 is the composition of the planting,M1 = Soil 100%, M2 = Cocopeat : Soil = 50% : 50%, M3 = Cocopeat : Soil = 75% : 25% and M4 = Soil : Cocopeat = 25% : 75% . The data obtained from the observations were analyzed using the F test of analysis with a level of 5%. If the test results have a significant effect, then proceed with the BNJ with a level of 5%. The results giving a dose of poultry manure 15 tons ha-1 is the best and most optimal fertilizer dose for the growth of green lettuce plants.